Ekspropriasi Pemegang Saham Minoritas dalam Struktur Kepemilikan Ultimat - Baldric Siregar (The Indonesian Journal of Accounting Research, 2013)
Large shareholders establish control over a firm through pyramid structure and cross-holding among firms. Those types of ownership structure create divergence between cash flow rights and control rights. Large shareholders may have control over a firm despite little cash flow rights. This study investigates the effects of cash flow right and control right separation on firm value of Indonesian companies listed on the Indonesia Stock Exchange for the period of 2000 to 2004. I use cut-off point of 10 percent control rights to test those effects. The results show that cash flow rights have positive effect on firm value, suggesting that firm value increases as cash flow right of controlling shareholders increases. I  further test whether cash flow right leverage depends on the controlling shareholders' participation in firm management and the presence of the second controlling shareholder. Contrary to the expectation, the evidence shows that the coefficients on both interactions are insignificant.